The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/s1983-41952018000500013
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for pervious concrete mix design and laboratory tests

Abstract: Pervious concrete may be used for stormwater management since it allows the water to pass through its interconnected macropores into stormwater systems or soils below. However, there is a need for additional standards related to pervious concrete prior to its widespread use, and there are many aspects related to mix design for desired properties, compaction methods, and test procedures that are not yet completely understood. These variables may significantly affect the functional and mechanical performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Results indicated that compressive strength increased with fresh density, whereas porosity decreased simultaneously, whatever the number of compaction layers or blow pattern. Both parameters exhibited a clear linear dependence on fresh density, as pointed out in the literature (40,41). With the increase in A/C ratio, compressive strength and fresh density reduced for all mixes.…”
Section: Resultssupporting
confidence: 84%
“…Results indicated that compressive strength increased with fresh density, whereas porosity decreased simultaneously, whatever the number of compaction layers or blow pattern. Both parameters exhibited a clear linear dependence on fresh density, as pointed out in the literature (40,41). With the increase in A/C ratio, compressive strength and fresh density reduced for all mixes.…”
Section: Resultssupporting
confidence: 84%
“…However, for some researchers [12,[15][16][17][18][19], the permeability test may be performed with constant-head permeameter for specimens with high porosity and high permeability. On the other hand, other authors [20][21][22][23] perform the test using falling-head permeameter, regardless of the porosity level of the specimens. In this sense, mix design philosophies of pervious concrete are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Connectivity of pores can be negatively affected by the compaction method and energy due to its effect in the orientation and packing of ingredients and, hence, restriction of compaction is essential [29]. Impulsive compaction methods such as proctor hammer [17,28,[67][68][69] or Marshall hammer [41,66] are quite often used to compact porous concrete specimens for testing purposes. In the case of pavement application, pervious concrete is compacted using hand steel rollers with low compaction energy [66].…”
Section: Methods Of Compaction and Compaction Energymentioning
confidence: 99%